Body Mass Index and Physical Activity of High School Adolescents with Different Learning Motivation - Utama, Dimas Duta Putra; Doewes, Muchsin; Ekawati, Febriani Fajar; Riyadi, Slamet (Journal of Social Work and Science Education, 2023)
During adolescence, individuals experience significant physical growth and development with changes in body composition that can affect their physical activity and learning motivation. This study aims to determine the effect of body mass index (BMI) and physical activity (PA) on the learning motivation of physical education students aged 15-17 years in different schools. This research design uses a quantitative descriptive approach. The sample consisted of 202 male and female at high-school Students 1 Sukoharjo, Central Java, aged 15 to 17 years, selected through purposive sampling. The instruments used in the research were BMI variables, PA, and learning motivation. Using multinomial logistic regression analysis for data analysis it is possible to find physical education students' learning motivation in a different category from the BMI category and PA category based on the p-value (0.05). The results of the descriptive data found that the most BMI research samples were in the normal category with 45.0%, then PA was in the moderate category with 49.5% doing moderate PA, and the learning motivation of physical education students was in the high category with 42.6%. multinomial logistic regression analysis showed, 1) there was no effect of BMI categories on different learning motivations (p-value: 0.920); 2) there is an effect of PA categories on physical education students' learning motivation (p-value: 0.009); 3) there is a significant effect between the categories of BMI and PA categories on the learning motivation of different physical education students (p-value: 0.000). A higher percentage of BMI is associated with decreased PA. In addition, low learning motivation was observed among students with low levels of PA and a higher percentage of BMI in the overweight category.